2018
DOI: 10.3390/su10072239
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Economic Benefits of Industrial Natural Gas Use in South Korea

Abstract: Natural gas (NG) is an important input used in the industrial production of South Korea. Therefore, the government requires quantitative information to be provided about the economic benefits of industrial NG (ING) use to decide whether to invest in expanding the supply of ING or not. This manuscript tries to measure the economic benefits of NG use in the manufacturing industry by using a specific case in South Korea. For this purpose, a trans-log production function is estimated using the data collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…The WTP values obtained in this research make sense and are justified by both domestic and international comparisons among similar studies. While it is not easy to compare our research to that of Kim et al [24], both our research and theirs found that the natural-gas-related value is high. In addition, our natural-gas-related value estimates are somewhat higher than those of Damigos et al, Jang et al, Moreira and Caetano,and Kim et al [11,[21][22][23].…”
Section: Itemcontrasting
confidence: 45%
See 1 more Smart Citation
“…The WTP values obtained in this research make sense and are justified by both domestic and international comparisons among similar studies. While it is not easy to compare our research to that of Kim et al [24], both our research and theirs found that the natural-gas-related value is high. In addition, our natural-gas-related value estimates are somewhat higher than those of Damigos et al, Jang et al, Moreira and Caetano,and Kim et al [11,[21][22][23].…”
Section: Itemcontrasting
confidence: 45%
“…The health, climate, and nonhealth benefits were 9.7 million €, 8 million €, and 1053 million €, respectively, and the social costs were 1053 million €. In addition, Kim et al used the translog production function to find that the value of industrial natural gas (ING) was USD2.07 per m 3 , which was 3.61 times as much as the average price [24]. Though not directly estimating the WTP of natural gas, Woo et al found that Korean households were willing to pay USD1.80 per month to replace nuclear power with renewables or LNG [19].…”
Section: Literature Reviewmentioning
confidence: 99%